Self-monitoring of glucose: doctor's and patient's view - А. S. Pogorelova (Медицинский совет, 2014)
Self-monitoring of blood glucose is the main tool in the management of diabetes mellitus (DM) utilized by both doctor and patient. On the one hand, self-monitoring of blood glucose is necessary to achieve and maintain adequate glycemic control; on the other hand, it is an invasive and stressful procedure. In order to make self-monitoring of glucose effective, both doctor and patient need to be aware of its relevance, while blood glucose meters should be highly accurate and reproducible, as well as pain-minimizing and user-friendly.